hMutSα- and hMutLα-dependent phosphorylation of p53 in response to DNA methylator damage - Duckett, Derek R. (The National Academy of Sciences, 1999)
hMSH2⋅hMSH6 heterodimer (hMutSα) and hMLH1⋅hPMS2 complex (hMutLα) have been implicated in the cytotoxic response of mammalian cells to a number of DNA-damaging compounds, including methylating agents that produce O(6)-methylguanine (O(6)MeG) adducts. This study demonstrates that O(6)MeG lesions, in which the damaged base is paired with either T or C, are subject to excision repair in a reaction that depends on a functional mismatch repair system. Furthermore, treatment of human cells with the S(N)1 DNA methylators N-methyl-N-nitrosourea or N-methyl-N′-nitro-N-nitrosoguanidine results in p53 phosphorylation on serine residues 15 and 392, and these phosphorylation events depend on the presence of functional hMutSα and hMutLα. Coupled with the previous demonstration that O(6)MeG⋅T and O(6)MeG⋅C pairs are recognized by hMutSα, these results implicate action of the mismatch repair system in the initial step of a damage-signaling cascade that can lead to cell-cycle checkpoint activation or cell death in response to DNA methylator damage.